Óbito fetal e infantil evitável em Fernandópolis/SP: taxas e padrão espacial ao longo da pandemia da COVID-19 e anos anteriores - Silva, Carolina Guerra da Mota e (2023)
Objectives: To characterize fetal and infant mortality from preventable causes before and during the emergency situation caused by the pandemic of COVID-19 in Fernandópolis. Methods: This is a study with observational, descriptive, ecological design, using spatial analysis techniques. The research population was composed of all fetal and infant deaths recorded in the Mortality Information System in the period from January 1, 2018 to December 31, 2022. The study was submitted and approved by the Research Ethics Committee of the Federal University of São Carlos under Certificate of Ethical Appraisal Submission No. 63776122.0.0000.5504. After collecting the data of avoidable deaths and live births registered in the indicated period, we initially performed a descriptive analysis of the data, with data tabulation, calculation of absolute and relative frequencies. Subsequently, the geolocalization of cases was performed, which consisted of the geographic interpolation of the location of the case with the geographic feature of the municipality under study (digital census grid of the municipality). For this procedure, the Google Earth Pro® software API was used to obtain the respective geographic coordinates for the reported residential addresses (latitude and longitude). Finally, for figuring the findings, choropleth maps were constructed with the occurrence of preventable deaths by census sectors using the ArcGis software version 10.5. Results: Of the total 30 fetal deaths evaluated in the period, 14 (46.67%) were preventable, 13 (43.33%) were non-preventable and three (10.00%) were inconclusive. Of the 23 infant deaths evaluated in the period from 2018 to 2022, four (17.39%) were preventable, 17 (73.91%) were non-preventable, and two (10.00%) were inconclusive. The Fetal Mortality Rate (FMR) had been falling and from 2020 there was an increase, although the proportion between the first and the last year was lower, but remained in line with the live births line in the period. In the year 2021, 83.33% of fetal deaths were preventable. In the analysis of the Infant Mortality Rate (IMR), we noticed that it was quite low in 2018, when it had the highest number of live births (800), from then on it had a small increase until 2020 following the drop in births, but in 2021 it had a significant increase going from 4.34 to 15 per thousand live births and the proportion of preventable deaths was 27.27%. In the spatial pattern it was possible to observe that there are places that have a higher occurrence of preventable deaths. Conclusion: The study showed that there was an increase in avoidable fetal and infant mortality in the emergency period of COVID-19, however, avoidable fetal mortality was more frequent and with alarming occurrence at the end of the third trimester. The spatial analysis showed that there are areas in need of qualification of health actions.